Genome sequencing of Plasmodium malariae identifies continental segregation and mutations associated with reduced pyrimethamine susceptibility - Amy Ibrahim; Franziska Mohring; Emilia Manko; Donelly A. van Schalkwyk; Jody E. Phelan; Debbie Nolder; Steffen Borrmann; Ayola A. Adegnika; Silvia Maria Di Santi; Mohammad Shafiul Alam; Dinesh Mondal; Francois Nosten; et al. (Nature Communications)
Abstract Plasmodium malariae parasites are widely observed across the tropics and sub-tropics. This slow-growing species, known to maintain chronic asymptomatic infections, has been associated with reduced antimalarial susceptibility. We analyse 251 P. malariae genomes from 28 countries, and leveraging 131,601 high-quality SNPs, demonstrate segregation of African and Asian isolates. Signals of recent evolutionary selection were identified in genes encoding putative surface proteins (pmmsp1) and putative erythrocyte invasion proteins (pmdpap3, pmrbp2, pmnif4). Amino acid substitutions were identified in orthologs of genes associated with antimalarial susceptibility including 2 amino acid substitutions in pmdhfr aligning with pyrimethamine resistance mutations in P. falciparum. Additionally, we characterise pmdhfr mutation F57L and demonstrate its involvement in reduced susceptibility to pyrimethamine in an in vitro parasite assay. We validate CRISPR-Cas9 mediated ortholog replacement in P. knowlesi parasites to determine the function of pmdhfr mutations and demonstrate that circulating pmdhfr genotypes are less susceptible to pyrimethamine.